Женщина во фрейме-сценарии русских паремий - Olechno-Wasiluk, Joanna (Studia Rossica Posnaniensia, 2019)
The paper analyses the image of woman in the interpretative frame of Russian paremias. The author asks a number of questions: What role does the woman play in society and family? How is she treated by her husband? How do they treat their children? Who is the woman juxtaposed with? Who is she compared to? Answering these questions the author tries to reconstruct the image of woman functioning in the Russian awareness. This is the image passed from generation to generation in proverbs and sayings, which are the products of language, culture and awareness.